2012
DOI: 10.1159/000333799
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Contribution to Alzheimer’s Disease: Transcriptional and Epigenetic Mechanisms in Patients with Late-Onset Alzheimer’s Disease

Abstract: Background: Neurofibrillary tangles and senile plaques are hallmarks of Alzheimer’s disease (AD) although the molecular basis of their coexistence remains elusive. The peptidyl-prolyl cis/trans isomerase Pin1 acts on both tau and amyloid precursor protein to regulate their functions by influencing tau phosphorylation and amyloid precursor protein processing. Objective: In order to identify potential biomarkers for AD in easily accessible cells and to gain insight into the relationship between the brain and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 55 publications
0
20
1
Order By: Relevance
“…Interestingly, a depletion of the soluble form of Pin1 has been described in neurons from AD subjects [57, 65] and differences in Pin 1 molecular and biochemical parameters have been reported in PBMCs from late-onset AD (LOAD) compared with control subjects [66]. …”
Section: Peptidyl-prolyl Cis-/trans-isomerase Pin1 In Pbmcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a depletion of the soluble form of Pin1 has been described in neurons from AD subjects [57, 65] and differences in Pin 1 molecular and biochemical parameters have been reported in PBMCs from late-onset AD (LOAD) compared with control subjects [66]. …”
Section: Peptidyl-prolyl Cis-/trans-isomerase Pin1 In Pbmcsmentioning
confidence: 99%
“…In particular, in PBMCs from LOAD we observed a significant increase in Pin1 gene expression together with a significant decrease in gene promoter methylation [66]. …”
Section: Peptidyl-prolyl Cis-/trans-isomerase Pin1 In Pbmcsmentioning
confidence: 99%
See 1 more Smart Citation
“…79, 80, 81, 82, 83 Aside from its post-translational modifications, the expression levels of histones are also important for cell cycle control. 84 Here, we show that the expression of HIST1H1E was increased in the AD Hp, whereas the expression of HIST1H1D was increased in the AD pCx but decreased in the AD Cb.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Arosio and collaborators found upregulated Pin1 gene expression in PBMCs of late onset AD patients and significantly reduced percentage methylation of Pin1 gene promoter. In PBMCs of these patients, Pin1 quantity and activity tended to be reduced as well [86]. To explain this apparent divergent behavior, Wang [87] suggested that Pin1 reduction contributes first to the accumulation of hyperphosphorylated tau in AD patients, but successively Pin1 is over expressed to compensate for the increased formation of Aβ plaques.…”
Section: Pin1 Links Brain Impaired Glucose Metabolism and Neuronalmentioning
confidence: 99%